Directional Selection on Tree Seedling Traits Driven by Experimental Drought Differs Between Mesic and Dry Populations - Costa e Silva, João; Jordan, Rebecca; Potts, Brad M.; Pinkard, Elizabeth; Prober, Suzanne M. (Frontiers in Ecology and Evolution, 2021)
We evaluated population differences and drought-induced phenotypic selection on four seedling traits of the Australian forest tree Eucalyptus pauciflora using a glasshouse dry-down experiment. We compared dry and mesic populations and tested for directional selection on lamina length (reflecting leaf size), leaf shape, the node of ontogenetic transition to the petiolate leaf (reflecting the loss of vegetative juvenility), and lignotuber size (reflecting a recovery trait). On average, the dry population had smaller and broader leaves, greater retention of the juvenile leaf state and larger lignotubers than the mesic population, but the populations did not differ in seedling survival. While there was statistical support for directional selection acting on the focal traits in one or other population, and for differences between populations in selection gradient estimates for two traits, only one trait - lamina length - exhibited a pattern of directional selection consistent with the observed population differences being a result of past adaptation to reduce seedling susceptibility to acute drought. The observed directional selection for lamina length in the mesic population suggests that future increases in drought risk in the wild will shift the mean of the mesic population towards that of the dry population. Further, we provide evidence suggesting an early-age trade-off between drought damage and recovery traits, with phenotypes which develop larger lignotubers early being more susceptible to drought death. Such trade-offs could have contributed to the absence of population mean differences in survival, despite marked differentiation in seedling traits.